Effects of the weight of shoes on calf muscle simulation - I-Lin Wang; Yi-Ming Chen; Ke-Ke Zhang; Ming Gou; Jia-Qi Li; Yu-Hong Jiang (Journal of Foot and Ankle Research, 2020)
Abstract The current study investigated the effects of shoes of different weights on calf individual muscle contributions during a running cycle. Twenty male runners ran on a force platform with shoes of four different weights (175 g, 255 g, 335 g, and 415 g). The study evaluated runners’ lower extremity muscle forces under the four shoe weight conditions using a musculoskeletal modeling system. The system generates equality and inequality constraint equations to simulate muscle forces. The individual muscle contributions in each calf were determined using these muscle forces. Data were compared using one-way repeated-measure ANOVA. The results revealed significant differences in the contributions of the gastrocnemius lateralis. Post hoc comparisons revealed that running in the 175 g shoes resulted in a larger contribution of the gastrocnemius lateralis than running in the 415 g shoes during the braking phase. Therefore, wearing lightweight shoes while running may promote fatigue in the gastrocnemius muscle during the braking phase. The calf muscle activation results may indicate that an adaptation period is warranted when changing from heavy to lightweight shoes.